2014 47th Hawaii International Conference on System Sciences 2014
DOI: 10.1109/hicss.2014.222
|View full text |Cite
|
Sign up to set email alerts
|

Link Sharing on Twitter during Popular Events: Implications for Social Navigation on Websites

Abstract: The goal of this research is to explore how social media data can be used to help users find information on websites. This paper presents the first stage in this line of research and focuses on the characteristics of links (i.e. website URLs) shared on social media to recommend relevant and popular web pages within the website to others. Specifically, the paper reports on a study of Twitter messages ("tweets") during four different events. Tweets were collected and those containing links were analyzed. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…They also found that this occurred on both mobile devices and desktop computers, content was structured, and engagement was dependent on the TV broadcast. Other researchers have also investigated the space by looking at conversational trends during live events on twitter [14] and how live backchannel data can help improve the user experience by informing navigation [11]. Fandom discussions on Tumblr appear to be somewhat similar to backchannel discussions, but they occur on a much more varied timeline ranging from 'live' during a broadcast to years later.…”
Section: Social Networking Motivations and Usagementioning
confidence: 99%
See 1 more Smart Citation
“…They also found that this occurred on both mobile devices and desktop computers, content was structured, and engagement was dependent on the TV broadcast. Other researchers have also investigated the space by looking at conversational trends during live events on twitter [14] and how live backchannel data can help improve the user experience by informing navigation [11]. Fandom discussions on Tumblr appear to be somewhat similar to backchannel discussions, but they occur on a much more varied timeline ranging from 'live' during a broadcast to years later.…”
Section: Social Networking Motivations and Usagementioning
confidence: 99%
“…We also found that nobody has studied Tumblr fandoms before. While other studies have looked into online backchannels of live entertainment events by investigating other microblogging sites such as Twitter [5,11,14], Tumblr fandom blogging has yet to be explored from a design perspective. This is despite the activity's dominance as one of the main types of Tumblr usage.…”
Section: Introductionmentioning
confidence: 99%
“…Link related research investigates link usage properties [26] as well as spam and security issues [7]. [6] studied the characteristics of links shared in Twitter to improve website navigation for large sport events. The study found that 25-47% of all of the tweets analyzed contained links, and the number of links shared was affected by the type of the event and the characteristics of the official website.…”
Section: Modeling User Behaviormentioning
confidence: 99%
“…The limited length of messages causes people to adopt different strategies, from retweets to links to full articles, websites, pictures, and videos, to share much more information than 140 characters could alone. People frequently include links in tweets to share links to sites, articles, videos, and images [6]. [7] found that 25% -29% of tweets posted daily contain links.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of research on hashtags, which elaborate on the relation between specifi c events, concepts, or social groups and on the hashtags used for them (for example, Romero et al 2011 ). Although it has been the subject of a few social navigation-related research projects (for example, Nizam et al 2014 ), the use of hashtags is yet to be explored in much more depth to understand how people behave in the digital realm.…”
Section: Especially After William Gibson Developed the Concept Of Cybmentioning
confidence: 99%